Hubungan Peningkatan Berat Badan Dengan Penggunaan Alat Kontrasepsi Suntikan 3 Bulan di Puskesmas Sudiang Tahun 2023 - Leli Leli (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Many women have found difficult in determining contraception tools, since there is no much safe and effective contraception. One contraceptive method which is considered to be quite ideal is that 3 month contraceptive injection. 3 month contraceptive injection is a type of contraceptive injection containing only progestin, it is injected every 3 months. There are lots of benefits from the using of this contraceptive. Nevertheless, there are also several weaknesses of this contraceptive, one of them is that the matter of weight gain. Based on that finding, it takes a study that aims to determine the correlation between weight gain and the use of contraceptive injections 3 month in Puskesmas Sudiang year of 2023. This type of research is analytic survey through cross sectional study. The sample in this study taken by purposive sampling, the number of samples in this study were 52 respondents. The research instrument was observation sheet, in which it was analyzed through Chi square test. The results of this study showed that there is a significant correlation between weight gain and the use of contraceptive injections of 3 month, it is showed P = 0.00 < ɑ = 0.05. Thus, when we use the 3 month contraceptive injection, it should be followed by the changing of lifestyle such as healthy diet, rest frequent and regular exercise.